Expertons and uncertain averaging operators versus correlational approaches: A case study on corporate social responsibility and effectiveness. Issue 1 (9th January 2017) - Yepes-Baldó, Montserrat; Boria-Reverter, Sefa; Romeo, Marina; Torres, Luis
Abstract : Purpose: The purpose of this paper is to explore the relationship between corporate social responsibility (CSR), work-life balance (WLB) and effectiveness by comparing a correlational approach, expertons method and uncertain averaging operators (uncertain average [UA], uncertain weighted average [UWA], uncertain probabilistic aggregation [UPA] and uncertain probabilistic weighted averaging [UPWA]). Design/methodology/approach: Participants were 814 employees from two Chilean companies with different levels of development on CSR policies. The Survey work–home Interaction – Nijmegen for Spanish Speaking Countries and the balanced scorecard were used. Results showed differences between companies with different levels of CSR development on individual effectiveness and relations between WLB and individual effectiveness. Findings: Expertons methodology and uncertain averaging operators allow more accurate results than correlational statistics. Originality/value: Expertons method and uncertain averaging operators (UA, UWA, UPA and UPWA) are common in the field of economics and engineering but very innovative in the human resources research, allowing more accurate analyses of workers' perceptions.